Chromosome-Level Comprehensive Genome of Mangrove Sediment-Derived Fungus Penicillium variabile HXQ-H-1 - Ling Peng (Journal of Fungi, 2019)
Penicillium is an ascomycetous genus widely distributed in the natural environment and is one of the dominant fungi involved in the decomposition of mangroves, which can produce a variety of antitumor compounds and bioactive substances. However, in mangrove ecosystems there is no complete genome in this genus. In this study, we isolated a fungus strain named Penicillium variabile HXQ-H-1 from coast mangrove (Fujian Province, China). We generated a chromosome-level genome with total size of 33.32 Mb, scaffold N50 of 5.23 Mb and contig N50 of 96.74 kb. Additionally, we anchored about 95.91% assembly sequences into the longest seven scaffolds, and predicted 10,622 protein-coding genes, in which 99.66% could be annotated by eight protein databases. The secondary metabolites analysis reveals the strain has various gene clusters involving polyketide synthase (PKS), non-ribosomal peptide synthetase (NRPS) and terpene synthase that may have a largely capacity of biotechnological potential. Comparison genome analysis between Penicillium variabile and Talaromyces islandicus reveals a small difference in the total number of genes, whereas HXQ-H-1 has a higher gene number with COG functional annotation. Evolutionary relationship of Penicillum based on genome-wide data was carried out for the first time, showing the strain HXQ-H-1 is closely related to Talaromyces islandicus. This genomic resource may provide a new resource for development of novel bioactive antibiotics, drug candidates and precursors in Penicillium variabile.